Hubungan Tingkat Pengetahuan dan Sikap dengan Tindakan Pencegahan Infeksi Soil Transmitted Helminth Memakai Obat Cacing Pada Siswa SDN 095252 Dan SDN 097658 Bandar Pulo, Kecamatan Bandar Kabupaten Simalungun - Novita Hasiani Simanjuntak (Nommensen Journal of Medicine, 2020)
According to WHO, in 2018, more than 1.5 million people (24% of the world's population) were infected by Soil Transmitted Helminthiasis (STH). more than 267 million of pre-school and school-aged children in this area are continually infected, need prevention and treatment interventions. WHO recommends giving antihelmintic drug without initial examination in endemic areas. namely Albendazol and Mebendazol, because they are effective, inexpensive, and easy to administer, even if not by health workers. Research in the form of cross-sectional design. This research was conducted at SDN 095252 and SDN 097658 Bandar Pulo Village, Bandar District, Simalungun Regency, from April to August 2019. The target population was elementary school students in Bandar District, Simalungun District. Affordable population is SDN 095252 students with 80 students and SDN 097658 with 139 students. The selection of research subjects with simple random sampling technique. In this study a sample of 120 respondents was obtained. This study uses a questionnaire as a measurement tool for all variables, with the median as a cut-off point for good and bad values, because the data is not normally distributed. Students with poor knowledge have a greater percentage than those who have good knowledge (55%). The attitude of good and bad students has a balanced percentage. The percentage of students who experienced signs and symptoms of helminthiasis was 82.5%, and the percentage of students who did not receive helminthic prevention had a greater percentage than those who received (65.8%). Prevention by giving worm medicine, the highest percentage is that students have been given worm medicine, but it has been given more than 6 months ago, that is equal to 57.5%. The results of bivariate analysis show that there is a significant relationship between the level of knowledge and prevention with the administration of worm medicine (p = 0.035), and there is no significant relationship between attitude and prevention with the administration of worm medication (p = 0.248). The conclusion of the research is that there is a significant relationship between the level of knowledge and prevention by giving worm medicine, and there is no significant relationship between attitude and prevention by giving worm medicine.